The Change in Fatty Acids and Sugars Reveals the Association between Trifoliate Orange and Endophytic Fungi - Meng, Lu-Lu; Liu, Rui-Cheng; Yang, Liu; Zou, Ying-Ning; Srivastava, Anoop Kumar; Kuča, Kamil; Hashem, Abeer; Abd Allah, Elsayed Fathi; Giri, Bhoopander; Wu, Qiang-Sheng (Journal of fungi (Basel, Switzerland), 2021)
Endophytes have the ability to improve plant nutrition alongside their agronomic performance, among which arbuscular mycorrhizal fungi provide the most benefits to their host. Previously, we reported for the first time that an arbuscular mycorrhizal-like fungus Piriformospora indica had the ability to colonize roots of trifoliate orange (Poncirus trifoliata) and conferred positive effects on nutrient acquisition. Present study showed the changes in fatty acids and sugars to unravel the physiological and symbiotic association of trifoliate orange with P. indica and an arbuscular mycorrhizal fungus, Funneliformis mosseae singly or in combination. All the endophytic fungi collectively increased fructose, glucose, and sucrose content in leaves and roots, along with a relatively higher increase with P. indica inoculation than with F. mosseae alone or dual inoculation. Treatment with P. indica increased the concentration of part unsaturated fatty acids such as C18:3N6, C20:2, C20:3N6, C20:4N6, C20:3N3, C20:5N3, C22:1N9, and C24:1. Additionally, P. indica induced the increase in the concentration of part saturated fatty acids such as C6:0, C8:0, C13:0, C14:0, and C24:0. F. mosseae hardly changed the content of fatty acids, except for increase in C14:0 and C20:5N3. Double inoculation only reduced the C21:0, C10:0, C12:0, C18:3N3, and C18:1 content and increased the C20:5N3 content. These endophytic fungi up-regulated the root PtFAD2, PtFAD6, PtΔ9, and PtΔ15 gene expression level, coupled with a higher expression of PtFAD2 and PtΔ9 by P. indica than by F. mosseae. It was concluded that P. indica exhibited a stronger response, for sugars and fatty acids, than F. mosseae on trifoliate orange. Such results also reveal the Pi (an in vitro culturable fungus) as a bio-stimulator applying to citriculture.
Keywords: fatty acid; endophytes; symbiosis; citrus; carbohydrate